Characterization and phylogenetic analysis of Acheilognathus chankaensis mitochondrial genome - Jin Tan; Zifeng Yin; Haijun Huang; Cong Zeng (Mitochondrial DNA. Part B. Resources, 2019)
A complete mitogenome of Acheilognathus chankaensis was assembled and analyzed in this study. The genome, with the length of 16,926 bp, contains 20 tRNAs, 13 coding genes, two rRNAs, and a D-loop region. The components of the genome are the same as available Acheilognathus mitogenomes in NCBI database, and GC (%) is also similar with other published mitogenomes in this genus. Phylogenetic analysis showed that A. chankaensis was genetically closed to A. macropterus. This complete mitogenome could contribute to the future phylogenetic and phylogeographic studies of genus Acheilognathus.